Comparative Study Thymol Oil and Some Gel Face Washing on Resistance Propionibacterium Acnes (Indian Journal of Forensic Medicine & Toxicology, 2021)
Acne is elevated of skin secretion with hyperkeratosis causing Propionibacterium acnes. The goal of studywas to assess the anti-inflammatory, and antibacterial potential of Thymol oil compare Gel face ,and is themain bacterium involved in the acne. The unpredictable use of antibiotics for the treatment of acne may endup within the advancement of bacterial resistance.